Pengaruh Short Waiting Time, Interpersonal Communication, Environment, dan Service Quality Terhadap Tingkat Kepuasan Pasien di Poli Gigi RSUD Kanjuruhan, Kabupaten Malang, Jawa Timur - Victreza, Dellaura Mercia; Bernarto, Innocentius (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to determine the effect of the variable SHORT WAITING TIME, INTERPERSONAL CUMMUNICATION, SERVICE QUALITY , Service quality on patient satisfaction at RSUD Kanjuruhan’s Dental Clinic. The model of this research was tested on a population of outpatients who had received treatment using a purposive sampling technique and obtained a sample size of 389 people in the period 15 November 2023 – 15 February 2024. Data collection was carried out online via a Google Form questionnaire using a Likert scale of 1 -5. The analysis method uses the SEM-PLS (Structural Equation Modelling based on Partial Least Square) technique using the SmartPLS 4.0 application. The results of this study show that: (1) there is a significant positive effect between short waiting time and patient satisfaction at RSUD Kanjuruhan’s Dental Clinic, (2) there is a significant positive effect between interpersonal communication and patient satisfaction at RSUD Kanjuruhan’s Dental Clinic Poly, (3) there is the influence is not positive and not significant effect between environmentand patient satisfaction at RSUD Kanjuruhan’s Dental Clinic, (4) there is a significant positive effect between service quality and patient satisfaction at RSUD Kanjuruhan’s Dental Clinic